A new species of Beebeomyia Curran (Diptera: Richardiidae) from Brazil, with description of immature stages and notes on their association with Taccarum ulei (Araceae) - Wendt, Lisiane Dilli; Gonçalves, Eduardo Gomes; Maia, Artur Campos Dália (Zootaxa, 2018)
A new species of the genus Beebeomyia Curran found in the northern coastal region of the state of Pernambuco, northeastern Brazil is described and illustrated, including characteristics of the male and female terminalia, third instar larva and puparium. This new species is only the second record for the genus in Brazil and broadens its occurrence to the Atlantic Forest ecoregion. Beebeomyia taccarivora sp. nov. is straightforwardly distinguishable from all other known species of Beebeomyia for exhibiting an entirely yellowish orange thorax with a central brown-colored stripe on the scutum, and a brownish orange abdomen with a central brown stripe on tergites 1–4. Similarly to what had been previously described for congenerics, female B. taccarivora flies exclusively use the inflorescences of their host plant, Taccarum ulei, as oviposition and brooding sites. Developing larvae feed on living floral tissue and pollen, and pupariation occurs within the inner surface of the spathe.